(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The study area was Shanuhar village of Babugonj Upazila of Barisal district, which was selected purposively based on agronomic suitability of growing Rabi crops. Necessary data were collected through focus group discussion (FGD) with 30 farmers including small, medium, and large farm households, school teachers, village leaders all the remaining by using pre design check list and structure schedule during May 2007 considering Rabi season of 2006-2007. Usually, farmers of the village could not sow their crops within the optimum time. They transplanted Aman rice in late due to inundation of land and planting of Rabi crops in late because of land unsuitability and long duration of T. Aman rice. Boro rice was adopted about 75% of the cropped area in Rabi season and but yield was low because of inadequate irrigation facilities. In contrast wheat needs comparatively less irrigation than Boro rice. Moreover, mungbean, mustard, lentil and grass pea produce reasonability good yield in rainfed condition. About 20- 25 % land become suitable for seeding wheat by first week of December after harvesting NfV T. Aman which indicated good prospect of growing wheat in the study village. Wheat is a more profitable Rabi crop than other crops like grass pea, mustard, lentil. Farmers earned the highest per hectare gross return (Tk.98646) and gross margin (Tk.22870) from the Wheat Aus rice -T. Aman rice pattern whereas Boro rice - Fallow - T. Aman pattern produced the lowest gross return (Tk.65918) and gross margin (Tk.10134). Higher benefit was achieved from the pattern Wheat Aus rice -T. Aman rice because of less production cost and high price of wheat grain, though three cereals crops could exhaust soil nutrient so that Mungbean-Aus rice T. Aman pattern may be alternate option to sustain soil health as well as productivity of the selected area. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11177 Bangladesh J. Agril. Res. 37(1): 55-65, March 2012